A comprehensive review and outlook of bifacial photovoltaic (bPV) technology. (1st November 2020) - Gu, Wenbo; Ma, Tao; Ahmed, Salman; Zhang, Yijie; Peng, Jinqing
Highlights: A comprehensive review on bifacial photovoltaic (bPV) technology is conducted. Technology, modelling, simulation, experiments, and evaluation are covered for bPV. A proper tilt angle with tracking, high albedo, elevation and row space is suggested. Various constrains of bPV technology, especially electrical mismatch are discussed. Abstract: Bifacial photovoltaic (bPV) technology is regarded as a promising alternative, as it can generate more power than conventional mono-facial PV (mPV) technology by absorbing sunlight from both sides. However, reviews on bPV are limited. Challenges, such as complex mechanisms, non-uniform rear-side irradiance and other issues constrain the bPV development. Therefore, it is necessary to present an overview on recent bPV development from various perspectives and provide some potential directions for future research. Therefore, an overview of bPV is demonstrated in this study, including its working principle, basic structure, cell categories, energy losses, merits and demerits. Moreover, recent research on bPV technology is discussed with respect to numerical modelling, software simulation, experimentation, economics, involved parameter analyses, performance characterization and system applications. Finally, some future perspectives and potential approaches are proposed for future research and to make bPV technology more cost-effective and competitive, since the current levelized cost of energy of bPV is only 2–6% lower than conventional mPV systems.